Glimpses Into the History of Interlingual Simultaneous Theater Interpreting in Estonia - Sibul, Karin (Journal of Audiovisual Translation, 2020)
This paper examines the practice of simultaneous interpretation of theater performances, in particular between Estonian and Russian, in Estonia over 70 years. This type of interpreting has not received much scholarly attention; rather, studies have mostly focused on the sign language interpretation of theater performances for the deaf community. I conducted interdisciplinary historical research relying on the oral history method to help preserve the fast-disappearing oral heritage of theater interpreting. This paper distinguishes between two periods in theater interpreting in Estonia, as determined by two drastically different sociopolitical periods in Estonia’s history. Drawing upon a total of 88 interviews with interpreters, people who recruited interpreters, and audience members, I identified and interviewed a total of 15 theater interpreters. I also analysed newspaper articles and performance schedules, which usually yielded single-word mentions of interpretation having taken place. This paper examines answers to the questions of who interpreted what, how, and when, and reaches the conclusion that theater interpreting can be a tool to bridge a gap between two communities as well as to facilitate integration in the same cultural space.